A Multi-Band/UWB MIMO/Diversity Antenna with an Enhanced Isolation Using Radial Stub Loaded Resonator - Li, Yingsong; Li, Wenxing; Yu, Wenhua (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper a multi-band/Ultra- Wideband (UWB) Multiple Input Multiple Output (MIMO) antenna, which is composed of two identical microstrip fed triple notch band UWB antennas and a Radial Stub Loaded Resonator (RSLR), is proposed and verified numerically and experimentally. The antenna is designed to meet the requirement of multi-band/UWB communication applications. A Defected Microstrip Structure (DMS) Band-Stop Filter (BSF) and an invert ?-shaped slot are employed to design the triple notch band UWB antenna. The resonance characteristics of the DMS-BSF and the band notch functions are presented to realize the proposed triple notch band UWB antenna. The isolation of the multi-band/UWB-MIMO antenna has been enhanced by inserting an RSLR loaded T-shaped stub between two identical triple notch band antennas. Both simulation and measurement results are presented to illustrate the performances of the proposed multi-band/UWB-MIMO antenna.